Searching for chronic hepatitis B patients in a low prevalence area – role of racial origin - Ono-Nita, Suzane Kioko (BioMed Central, 2004)
BACKGROUND: Clinical studies for testing new drugs against hepatitis B ought to be carried out in low prevalence areas despite difficulties on patient recruitment. In such areas, relatives of chronic hepatitis B patients are considered to be at risk of acquiring the hepatitis B virus (HBV). The aim of this study was to evaluate the prevalence of HBV markers (anti-HBc, HBsAg and anti-HBs) in familial members of chronic hepatitis B (CHB) patients according to their origin (Asian or Western) in a low prevalence area, the city of São Paulo, Brazil. METHODS: Twenty three Asian CHB probands and their 313 relatives plus 31 CHB probands of Western origin and their 211 relatives were screened for HBV serological markers; the study was carried out in the outpatient clinic of the University of São Paulo School of Medicine. RESULTS: Mother to child transmission was greater in the Asian group whereas sexual transmission was more frequent in the Western group (p < 0.0001). Anti-HBc was positive in 90% and 57% of the Asian and Western parents (p = 0.0432) and in 97% and 33% of the Asian and Western brothers (p = 0.0001), respectively. HBsAg was more frequent among the Asian (66%) than the Western (15%) mothers (p = 0.0260) as well as among the Asian (81%) than the Western (19%) brothers (p = 0.0001). We could detect 110 new HBsAg-positive subjects related to the 54 index patients, being the majority (81%) of Asian origin. CONCLUSION: In low prevalence area of hepatitis B, family members and household contacts of chronic HBV carriers are at high risk for acquiring hepatitis B.